A water-based zinc ion electrolyte containing a functional additive, a preparation method and application thereof
Patent Information
- Application Number
- CN202511463120.X
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-10-14
- Publication Date
- 2026-10-30
AI Technical Summary
但这些路线存在配方复杂、添加剂间可能相互影响、以及对于负极保护机理相对单一(主要依赖物理吸附)等问题
[0050]1、本发明在水系锌离子电解液中加入功能性添加剂三氟甲磺酸金属盐M(OTf)n,其中非锌的金属阳离子Mn+调节电解液中锌离子的溶剂化结构,减少锌离子周围的结合水,从而抑制其在锌负极表面沉积/剥离时的析氢反应,减少有害副产物的产生,提高水系锌离子电池循环过程的可逆性和延长循环寿命。
Smart Images

Figure CN123018171A_ABST
Abstract
Description
Technical Field
[0001] This invention belongs to the field of electrochemical energy storage technology, and relates to an aqueous zinc ion electrolyte containing functional additives, its preparation method and application. Background Technology
[0002] Aqueous zinc-ion batteries (AZIBs) have shown great promise for large-scale energy storage due to their high safety, low cost, environmental friendliness, and abundant zinc resources. However, their commercialization is still limited by two key challenges: First, zinc metal anodes are prone to dendrite growth, hydrogen evolution, and corrosion in aqueous electrolytes, leading to low coulombic efficiency, short cycle life, and even short-circuit risks. Second, cathode materials (such as vanadium-based and manganese-based oxides) are prone to structural dissolution or collapse during cycling, resulting in rapid capacity decay. Using iodine cathodes, on the other hand, faces problems such as polyiodide ions shutting through the separator to the zinc anode, leading to loss of active material, zinc corrosion, and self-discharge.
[0003] To address these challenges, existing technologies have proposed various solutions. Current research has reported the use of organic polymers (such as carboxymethyl cellulose and hydroxypropyl methyl cellulose) to improve the behavior of the zinc anode through surface adsorption, the use of inorganic metal salts (such as magnesium sulfate and aluminum sulfate) to stabilize the cathode structure, or the use of a combination of inorganic metal salts and aqueous organic additives to simultaneously stabilize the structures of both the anode and cathode. However, these approaches suffer from problems such as complex formulations, potential interactions between additives, and a relatively singular anode protection mechanism (primarily relying on physical adsorption).
[0004] Therefore, there is an urgent need in this field for a new technology solution that can efficiently and simultaneously solve the problem of the positive and negative electrode interface, and also has the advantages of simple process and easy industrialization. Summary of the Invention
[0005] The purpose of this invention is to address the aforementioned problems in the prior art by proposing an aqueous zinc-ion electrolyte comprising zinc salts and functional additives. The functional additives include non-zinc metal cations and trifluoromethanesulfonate anions. The non-zinc metal cations can regulate the solvation structure of zinc ions in the aqueous electrolyte and embed or adsorb into the cathode material to stabilize its crystal structure and improve the performance of the aqueous zinc-ion battery.
[0006] One objective of this invention is achieved through the following technical solution:
[0007] An aqueous zinc ion electrolyte containing functional additives includes: zinc salt, functional additives, and solvent;
[0008] The functional additive is a trifluoromethanesulfonic acid metal salt, wherein the metal element is selected from at least one of aluminum (Al), magnesium (Mg), manganese (Mn), tin (Sn), and indium (In);
[0009] The concentration of the functional additive in the aqueous zinc ion electrolyte containing the functional additive is 0.01-1 mol / L.
[0010] Preferably, the zinc salt is selected from at least one of zinc sulfate, zinc nitrate, zinc trifluoromethanesulfonate, zinc bis(trifluoromethanesulfonyl)imide, zinc chloride, zinc acetate, and zinc perchlorate.
[0011] Further preferably, the zinc salt is zinc sulfate.
[0012] Preferably, the concentration of zinc salt in the aqueous zinc ion electrolyte is 0.1-5 mol / L.
[0013] More preferably, the concentration of the zinc salt is 0.5-3 mol / L.
[0014] More preferably, the concentration of the zinc salt is 2 mol / L.
[0015] Preferably, the concentration of the functional additive in the aqueous zinc ion electrolyte is 0.05-0.3 mol / L.
[0016] Further preferably, the concentration of the functional additive is 0.1 mol / L.
[0017] Preferably, in the aqueous zinc ion electrolyte, the concentration of the zinc salt is greater than the concentration of the functional additive.
[0018] Preferably, the solvent is water.
[0019] Preferably, the functional additive is a metal trifluoromethanesulfonate salt M(OTf). n , 0 < n ≤ 3.
[0020] Preferably, the functional additive includes metal cation M. n+ and trifluoromethanesulfonic acid anion [OTf] - .
[0021] Preferably, the functional additive is at least one selected from aluminum trifluoromethanesulfonate, magnesium trifluoromethanesulfonate, manganese trifluoromethanesulfonate, tin trifluoromethanesulfonate, and indium trifluoromethanesulfonate.
[0022] Further preferably, the functional additive is aluminum trifluoromethanesulfonate.
[0023] The second objective of this invention is achieved through the following technical solution:
[0024] A method for preparing an aqueous zinc ion electrolyte containing functional additives includes: dissolving the functional additives in water in an inert gas environment, and then adding zinc salts to obtain the aqueous zinc ion electrolyte containing functional additives.
[0025] Preferably, the preparation method includes: dissolving the functional additive in 50-60 vol% water in an inert gas environment, adding zinc salt to the solution in batches while continuously stirring, and then adding the remaining water to obtain an aqueous zinc ion electrolyte containing the functional additive.
[0026] The third objective of this invention is achieved through the following technical solution:
[0027] An aqueous zinc-ion battery comprising the aforementioned aqueous zinc-ion electrolyte containing functional additives.
[0028] Preferably, the aqueous zinc-ion battery includes an aqueous zinc-ion symmetric battery, an aqueous zinc-ion half-cell, and an aqueous zinc-ion full-cell.
[0029] Further preferably, the aqueous zinc-ion symmetric battery includes an aqueous zinc-ion electrolyte containing functional additives, a diaphragm, and a zinc negative electrode sheet;
[0030] The aqueous zinc-ion half-cell includes a current collector, an aqueous zinc-ion electrolyte containing functional additives, a diaphragm, and a zinc negative electrode.
[0031] The aqueous zinc-ion full battery includes a positive electrode, an aqueous zinc-ion electrolyte containing functional additives, a separator, and a zinc negative electrode.
[0032] More preferably, the positive electrode material in the positive electrode sheet is selected from at least one of manganese-based compounds, vanadium-based compounds, nickel / cobalt-based compounds, elemental iodine, and composite materials;
[0033] The manganese-based compound is selected from at least one of α-MnO2, β-MnO2, γ-MnO2, α-Mn2O3, α-Mn3O4 and ZnMn2O4;
[0034] The vanadium-based compound is selected from VO2, V2O5, V3O7·H2O, and V6O. 13 V 10 O 24 ·12H2O, VS2, H2V3O8, LiV3O8, Zn 0.25 V2O5·nH2O, Zn2V2O7, Zn3V2O7(OH)2·2H2O, Ca 0.25 V₂O₅·nH₂O and Na₂V₆O 16 At least one of ·3H2O;
[0035] The nickel / cobalt-based compound is selected from at least one of NiO, Ni3S2, Ni(OH)2, NiCo2O4, Co3O4@NiO, NiAlCo layered double hydroxides and Co3O4;
[0036] The composite material is selected from at least one of CNT-MnO2, CNT-NiO, CNT-Co3O4, CNT-V2O5, CNT-NiCoMnO4, I2-PAC, I2-PANI, I2-CNT, I-PPy, and I2-MnO2.
[0037] More preferably, the current collector is selected from at least one of copper and copper alloys, aluminum and aluminum alloys, nickel and nickel alloys, stainless steel, carbon materials, and composite current collectors;
[0038] The copper and copper alloys include copper foil, copper mesh, or copper foam;
[0039] The aluminum and aluminum alloys include aluminum foil or etched honeycomb structure aluminum;
[0040] The nickel and nickel alloys include nickel foil or nickel foam;
[0041] The stainless steel includes stainless steel mesh or porous stainless steel;
[0042] The carbon material includes graphene, carbon fiber cloth, or carbon nanotubes.
[0043] The composite current collector includes conductive resin, carbon-coated aluminum foil, or titanium-nickel shape memory alloy.
[0044] More preferably, the diaphragm is selected from at least one of glass fiber diaphragm, polyethylene diaphragm, polypropylene diaphragm, or polyethylene / polypropylene composite multilayer diaphragm.
[0045] Preferably, the aqueous zinc-ion full battery includes an I2-PAC positive electrode, an aqueous zinc-ion electrolyte containing functional additives, a separator, and a zinc negative electrode.
[0046] Preferably, the aqueous zinc-ion full battery includes a CNT-MnO2 positive electrode, an aqueous zinc-ion electrolyte containing functional additives, a separator, and a zinc negative electrode.
[0047] Preferably, during operation, a fluoride protective layer is generated on the surface of the zinc negative electrode of the aqueous zinc-ion battery.
[0048] More preferably, the fluoride is at least one selected from aluminum fluoride, magnesium fluoride, manganese fluoride, tin fluoride, and indium fluoride.
[0049] Compared with the prior art, the present invention has the following beneficial effects:
[0050] 1. This invention involves adding a functional additive, metal trifluoromethanesulfonic acid salt M(OTf), to an aqueous zinc ion electrolyte. n Among them, the non-zinc metal cation M n+ By adjusting the solvation structure of zinc ions in the electrolyte and reducing the bound water around zinc ions, the hydrogen evolution reaction during their deposition / stripping on the zinc anode surface is inhibited, the generation of harmful byproducts is reduced, and the reversibility of the cycling process of aqueous zinc-ion batteries is improved and the cycle life is extended.
[0051] 2. During the operation of aqueous zinc-ion batteries, the combined action of the anions and cations of functional additives generates a fluoride MF protective layer on the surface of the zinc anode. Its shielding effect can further inhibit the corrosion and hydrogen evolution of the zinc anode. At the same time, the low nucleation energy barrier between it and the zinc (002) crystal plane can induce uniform and fine-grained zinc deposition, thereby further extending the cycle life of the battery.
[0052] 3. For the use of vanadium-based, manganese-based, and nickel / cobalt-based materials as the positive electrode material in aqueous zinc-ion batteries, the M in the functional additive... n+ Ions can be embedded or adsorbed into the cathode material to stabilize its crystal structure, alleviate its structural dissolution or collapse, and reduce capacity decay.
[0053] 4. For the use of iodine element / iodine-containing composite materials as the positive electrode material of aqueous zinc-ion batteries, the trifluoromethanesulfonate ions in the functional additives can react with polyiodide ions, adsorb and fix the polyiodide ions to suppress their shuttle effect on both sides of the diaphragm, thereby reducing problems such as loss of positive electrode active material, zinc corrosion and self-discharge. Attached Figure Description
[0054] Figure 1 Aqueous zinc-ion symmetric batteries assembled from the aqueous zinc-ion electrolyte containing functional additives of Example 1 and the aqueous zinc-ion battery electrolyte of Comparative Example 1, respectively, were tested at 1 mA·cm⁻¹. -2 1mAh·cm -2 The constant current charge-discharge test curve under the specified conditions.
[0055] Figure 2 The aqueous half-cells assembled from the aqueous zinc-ion electrolytes containing functional additives in Examples 1, 6, and 7 of this invention, respectively, were tested at 2 mA·cm⁻¹. -2 1mAh·cm -2 Coulomb efficiency diagram under the given conditions.
[0056] Figure 3 This is a comparison chart of the long-cycle curves of aqueous zinc-ion full cells assembled with the aqueous zinc-ion electrolyte containing functional additives of Example 1, the aqueous zinc-ion battery electrolyte of Comparative Example 1, and CNT-MnO2 positive electrode sheets under 3C rate conditions.
[0057] Figure 4 This is a comparison chart of the long-cycle curves of full cells assembled with the aqueous zinc-ion electrolyte containing functional additives of Example 1 of the present invention, the aqueous zinc-ion battery electrolyte of Comparative Example 1, and the I2-PAC positive electrode sheet, under 3C rate conditions.
[0058] Figure 5 The symmetrical battery assembled with the aqueous zinc ion electrolyte containing functional additives according to Example 1 of the present invention operates at 1 mA·cm⁻¹. -2 1mAh·cm -2 XPS spectra of zinc foil surface after 50 cycles of constant current charge and discharge under certain conditions: (a) F 1s, (b) Al 2s, (c) and (d) Al 2p.
[0059] Figure 6 The surface SEM images (a) of commercial zinc foil after immersion in the aqueous zinc ion electrolyte containing functional additives of Example 1 for 24 hours and (b) of the surface SEM image of the aqueous zinc ion battery electrolyte of Comparative Example 1 for 24 hours are shown. Detailed Implementation
[0060] The technical solution of the present invention will be further described and illustrated below through specific embodiments. It should be understood that the specific embodiments described herein are only for the purpose of helping to understand the present invention and are not intended to limit the present invention.
[0061] Unless otherwise specified, the raw materials used in the embodiments of the present invention are all commonly used in the art, and the methods used in the embodiments are all conventional methods in the art.
[0062] In one embodiment, a method for preparing an aqueous zinc ion electrolyte containing functional additives includes: accurately weighing trifluoromethanesulfonate in an argon-atmosphere glove box (water and oxygen content less than 0.1 ppm) at room temperature, transferring it in one go to 50-60% of the target volume of deionized water within 30 seconds, and stirring at 400-600 rpm for 10-20 minutes until a clear and transparent solution is obtained without heat release. Then, under continuous stirring at 300-400 rpm, adding zinc salt in 3-5 batches to the above transparent solution, with each batch spaced 2-3 minutes apart, controlling the solution temperature not to fall below 15°C, until the solution becomes completely clear and transparent again and the temperature returns to room temperature, then stopping stirring. Slowly adding the remaining deionized water to the bottle to make up the volume. Then continuing to stir and homogenize at 150-250 rpm for 30-60 minutes until the solution is homogeneous, obtaining the aqueous zinc ion electrolyte containing functional additives.
[0063] In this article, the manufacturer of the battery performance testing instrument is Wuhan Landian Electronics Co., Ltd., and the model is CT2001A 5V / 2mA.
[0064] The symmetrical battery assembly and testing method is as follows: two cells are assembled and tested. Disc-shaped Zn foils were used as counter electrodes. 140 μL of electrolyte was dropped onto a separator made of 850 μm thick Watman GF / B glass fiber material. CR2032 button cell half-cells were assembled in the order of Zn foil (+) || glass fiber separator + 140 μL electrolyte || Zn foil (-). Cyclic performance testing was performed on the above cells. The areal capacity was 1 mAh·cm³. -2 Current density 1 mA·cm -2 .
[0065] The half-cell assembly and testing method is as follows: Disc Cu foil as a current collector, A circular Zn foil was used as the counter electrode. 140 μL of electrolyte was dropped onto a separator made of 850 μm thick Watman GF / B glass fiber material. A CR2032 button cell was assembled in the order of Cu foil (+) || glass fiber separator + 140 μL electrolyte || Zn foil (-). Cyclic performance testing was performed on the above battery. The areal capacity was 1 mAh·cm³. -2 Current density 2 mA·cm -2 The discharge cutoff voltage is 0V, and the charging cutoff voltage is 0.6V.
[0066] The full battery assembly and testing method is as follows: CNT-MnO2 or I2-PAC positive electrode sheets are used as positive electrodes. A circular Zn wafer was used as the negative electrode. 140 μL of electrolyte was dropped onto a separator made of 850 μm thick Watman GF / B glass fiber material. The CR2032 button cell was assembled in the following order: CNT-MnO2 or I2-PAC(+) || glass fiber separator + 140 μL electrolyte || protective film (sputtered layer facing Zn foil) || Zn foil (-). The cells were subjected to 0.5C (initial 4 cycles) / 3C rate cycling performance tests. The discharge cutoff voltage was 0.6V, and the charge cutoff voltage was 1.6V.
[0067] Example 1
[0068] The aqueous zinc ion electrolyte containing functional additives in this embodiment includes ZnSO4 at a concentration of 2 mol / L and Al(OTf)3 at a concentration of 0.1 mol / L; the preparation method includes:
[0069] At room temperature, 474.2 mg of aluminum trifluoromethanesulfonate was dissolved in 6 mL of deionized water to obtain a clear and transparent solution. 5751.2 mg of zinc sulfate heptahydrate was added to the above solution and stirred until dissolved to obtain a clear and transparent solution. After the solution returned to room temperature, deionized water was added to a volume of 10 mL to obtain an aqueous zinc ion electrolyte containing functional additives.
[0070] The aqueous zinc-ion battery in this embodiment includes:
[0071] An aqueous zinc-ion symmetric battery was assembled using an aqueous zinc-ion electrolyte containing functional additives, a commercial zinc foil negative electrode, and a glass fiber separator, as described in this embodiment.
[0072] The aqueous zinc-ion half-cell was assembled using the aqueous zinc-ion electrolyte containing functional additives, a commercial copper foil current collector, a commercial zinc foil negative electrode, and a glass fiber separator in this embodiment.
[0073] An aqueous zinc-ion full cell was assembled using an aqueous zinc-ion electrolyte containing functional additives, a CNT-MnO2 positive electrode, a commercial zinc foil negative electrode, and a glass fiber separator, as described in this embodiment.
[0074] The preparation method of CNT-MnO2 cathode includes:
[0075] 0.15 g of carbon nanotubes were dispersed in 150 mL of deionized water, denoted as solution A. 2.94 g of manganese acetate was added to solution A and stirred vigorously. 1.27 g of potassium permanganate was added to 80 mL of deionized water, denoted as solution B. Solution A was added dropwise to solution B at a uniform rate, and after stirring until homogeneous, the mixture was introduced into a high-pressure reactor lined with polytetrafluoroethylene and heated at 120 °C for 12 h. The precipitate was collected and freeze-dried under vacuum to obtain the CNT-MnO2 cathode material. Powdered CNT-MnO2, SuperP, and sodium alginate were mixed at a mass ratio of 7:2:1 and stirred for 30 min to prepare a slurry. The slurry was coated onto carbon paper using a 400 μm thick scraper and dried at room temperature. Finally, the CNT-MnO2 cathode sheet was cut using a small punching machine.
[0076] Performance tests were conducted, and the results are shown in Table 1.
[0077] Example 2
[0078] The aqueous zinc ion electrolyte containing functional additives in this embodiment includes ZnSO4 at a concentration of 2 mol / L and Mg(OTf)2 at a concentration of 0.1 mol / L; the preparation method includes:
[0079] At room temperature, 322.4 mg of magnesium trifluoromethanesulfonate was dissolved in 6 mL of deionized water to obtain a clear and transparent solution. 5751.2 mg of zinc sulfate heptahydrate was added to the above solution and stirred until dissolved to obtain a clear and transparent solution. After the solution returned to room temperature, deionized water was added to a volume of 10 mL to obtain an aqueous zinc ion electrolyte containing functional additives.
[0080] Using the aqueous zinc-ion electrolyte containing functional additives of this embodiment, aqueous zinc-ion symmetric cells, aqueous zinc-ion half-cells, and aqueous zinc-ion full cells are assembled according to the steps of Example 1.
[0081] Performance tests were conducted, and the results are shown in Table 1.
[0082] Example 3
[0083] The aqueous zinc ion electrolyte containing functional additives in this embodiment includes ZnSO4 at a concentration of 2 mol / L and Mn(OTf)2 at a concentration of 0.1 mol / L; the preparation method includes:
[0084] At room temperature, 353.1 mg of manganese trifluoromethanesulfonate was dissolved in 6 mL of deionized water to obtain a clear and transparent solution. 5751.2 mg of zinc sulfate heptahydrate was added to the above solution and stirred until dissolved to obtain a clear and transparent solution. After the solution returned to room temperature, deionized water was added to a volume of 10 mL to obtain an aqueous zinc ion electrolyte containing functional additives.
[0085] Using the aqueous zinc-ion electrolyte containing functional additives of this embodiment, aqueous zinc-ion symmetric cells, aqueous zinc-ion half-cells, and aqueous zinc-ion full cells are assembled according to the steps of Example 1.
[0086] Performance tests were conducted, and the results are shown in Table 1.
[0087] Example 4
[0088] The aqueous zinc ion electrolyte containing functional additives in this embodiment includes ZnSO4 at a concentration of 2 mol / L and Sn(OTf)2 at a concentration of 0.1 mol / L; the preparation method includes:
[0089] At room temperature, 416.8 mg of stannous trifluoromethanesulfonate was dissolved in 6 mL of deionized water to obtain a clear and transparent solution. 5751.2 mg of zinc sulfate heptahydrate was added to the above solution and stirred until dissolved to obtain a clear and transparent solution. After the solution returned to room temperature, deionized water was added to a volume of 10 mL to obtain an aqueous zinc ion electrolyte containing functional additives.
[0090] Using the aqueous zinc-ion electrolyte containing functional additives of this embodiment, aqueous zinc-ion symmetric cells, aqueous zinc-ion half-cells, and aqueous zinc-ion full cells are assembled according to the steps of Example 1.
[0091] Performance tests were conducted, and the results are shown in Table 1.
[0092] Example 5
[0093] The aqueous zinc ion electrolyte containing functional additives in this embodiment includes ZnSO4 at a concentration of 2 mol / L and In(OTf)3 at a concentration of 0.1 mol / L; the preparation method includes:
[0094] At room temperature, 562.0 mg of indium trifluoromethanesulfonate was dissolved in 6 mL of deionized water to obtain a clear and transparent solution. 5751.2 mg of zinc sulfate heptahydrate was added to the above solution and stirred until dissolved to obtain a clear and transparent solution. After the solution returned to room temperature, deionized water was added to a volume of 10 mL to obtain an aqueous zinc ion electrolyte containing functional additives.
[0095] Using the aqueous zinc-ion electrolyte containing functional additives of this embodiment, aqueous zinc-ion symmetric cells, aqueous zinc-ion half-cells, and aqueous zinc-ion full cells are assembled according to the steps of Example 1.
[0096] Performance tests were conducted, and the results are shown in Table 1.
[0097] Example 6
[0098] Compared with Example 1, the difference is that the aqueous zinc ion electrolyte containing functional additives in this example includes ZnSO4 with a concentration of 2 mol / L and Al(OTf)3 with a concentration of 0.05 mol / L.
[0099] Using the aqueous zinc-ion electrolyte containing functional additives of this embodiment, aqueous zinc-ion symmetric cells, aqueous zinc-ion half-cells, and aqueous zinc-ion full cells are assembled according to the steps of Example 1.
[0100] Performance tests were conducted, and the results are shown in Table 1.
[0101] Example 7
[0102] Compared with Example 1, the difference is that the aqueous zinc ion electrolyte containing functional additives in this example includes ZnSO4 with a concentration of 2 mol / L and Al(OTf)3 with a concentration of 0.3 mol / L.
[0103] Using the aqueous zinc-ion electrolyte containing functional additives of this embodiment, aqueous zinc-ion symmetric cells, aqueous zinc-ion half-cells, and aqueous zinc-ion full cells are assembled according to the steps of Example 1.
[0104] Performance tests were conducted, and the results are shown in Table 1.
[0105] Example 8
[0106] In this embodiment, the positive electrode is an I2-PAC positive electrode, and its preparation method includes:
[0107] 300 mg of activated carbon (PAC) and 200 mg of iodine powder (I2) were mixed and ground for 10 min. The mixture was then placed in a vacuum-sealed glass tube and heated to 90 °C in a muffle furnace for 5 h to obtain I2-PAC powder. I2-PAC, Super P (carbon black conductive agent), and PVDF (polyvinylidene fluoride) were mixed at a mass ratio of 8:1:1, and 1.5 g of NMP was added and stirred for 30 min to obtain I2-PAC positive electrode slurry. The slurry was coated onto carbon paper with a 400 μm thick doctor blade and dried in a 60 °C forced-air drying oven for 6 h. The slurry was then cut into round sheets using a small punching machine to obtain I2-PAC positive electrode sheets.
[0108] An aqueous zinc-ion full cell was assembled using the aqueous zinc-ion electrolyte containing functional additives from Example 1, an I2-PAC positive electrode, a commercial zinc foil negative electrode, and a glass fiber separator.
[0109] Performance tests were conducted, and the results are shown in Table 1.
[0110] Example 9
[0111] Using the aqueous zinc-ion electrolyte containing functional additives from Example 2, an aqueous zinc-ion full battery was assembled according to the steps of Example 8.
[0112] Performance tests were conducted, and the results are shown in Table 1.
[0113] Example 10
[0114] Using the aqueous zinc-ion electrolyte containing functional additives from Example 3, an aqueous zinc-ion full battery was assembled according to the steps of Example 8.
[0115] Performance tests were conducted, and the results are shown in Table 1.
[0116] Example 11
[0117] Using the aqueous zinc-ion electrolyte containing functional additives from Example 4, an aqueous zinc-ion full battery was assembled according to the steps of Example 8.
[0118] Performance tests were conducted, and the results are shown in Table 1.
[0119] Example 12
[0120] Using the aqueous zinc-ion electrolyte containing functional additives from Example 5, an aqueous zinc-ion full battery was assembled according to the steps of Example 8.
[0121] Performance tests were conducted, and the results are shown in Table 1.
[0122] Example 13
[0123] Using the aqueous zinc-ion electrolyte containing functional additives from Example 6, an aqueous zinc-ion full battery was assembled according to the steps of Example 8.
[0124] Performance tests were conducted, and the results are shown in Table 1.
[0125] Example 14
[0126] Using the aqueous zinc-ion electrolyte containing functional additives from Example 7, an aqueous zinc-ion full battery was assembled according to the steps of Example 8.
[0127] Performance tests were conducted, and the results are shown in Table 1.
[0128] Comparative Example 1
[0129] The aqueous zinc ion electrolyte in this comparative example comprises ZnSO4 with a concentration of 2 mol / L; the preparation method includes:
[0130] At room temperature, 5751.2 mg of zinc sulfate heptahydrate was added to 6 mL of deionized water and stirred until a clear, transparent solution was obtained. After the solution returned to room temperature, deionized water was added until the solution volume was 10 mL, yielding an aqueous zinc ion electrolyte.
[0131] Using the aqueous zinc-ion electrolyte of this comparative example, an aqueous zinc-ion symmetric cell, an aqueous zinc-ion half-cell, and an aqueous zinc-ion full cell were assembled according to the steps of Example 1.
[0132] Performance tests were conducted, and the results are shown in Table 1.
[0133] Comparative Example 2
[0134] The aqueous zinc ion electrolyte in this comparative example comprises Zn(OTf)₂ with a concentration of 2 mol / L; the preparation method includes:
[0135] At room temperature, 7270.1 mg of zinc trifluoromethanesulfonate was added to 6 mL of deionized water and stirred until a clear, transparent solution was obtained. After the solution returned to room temperature, deionized water was added until the solution volume was 10 mL, yielding an aqueous zinc ion electrolyte.
[0136] Using the aqueous zinc-ion electrolyte of this comparative example, an aqueous zinc-ion symmetric cell, an aqueous zinc-ion half-cell, and an aqueous zinc-ion full cell were assembled according to the steps of Example 1.
[0137] Performance tests were conducted, and the results are shown in Table 1.
[0138] Comparative Example 3
[0139] The aqueous zinc ion electrolyte of this comparative example includes ZnSO4 at a concentration of 2 mol / L and Zn(OTf)2 at a concentration of 0.1 mol / L; the preparation method includes:
[0140] At room temperature, 363.5 mg of zinc trifluoromethanesulfonate was dissolved in 6 mL of deionized water to obtain a clear solution for later use. 5751.2 mg of zinc sulfate heptahydrate was added to the above solution and stirred until a clear, transparent solution was obtained. After the solution returned to room temperature, deionized water was added to a volume of 10 mL to obtain an aqueous zinc ion electrolyte.
[0141] Using the aqueous zinc-ion electrolyte of this comparative example, an aqueous zinc-ion symmetric cell, an aqueous zinc-ion half-cell, and an aqueous zinc-ion full cell were assembled according to the steps of Example 1.
[0142] Comparative Example 4
[0143] The aqueous zinc ion electrolyte of this comparative example comprises 2 mol / L ZnSO4 and 0.05 mol / L Al2(SO4)3; the preparation method includes:
[0144] At room temperature, 171.1 mg of aluminum sulfate was dissolved in 6 mL of deionized water to obtain a clear solution for later use. 5751.2 mg of zinc sulfate heptahydrate was added to the above solution and stirred until a clear, transparent solution was obtained. After the solution returned to room temperature, deionized water was added to a volume of 10 mL to obtain an aqueous zinc ion electrolyte.
[0145] Using the aqueous zinc-ion electrolyte of this comparative example, an aqueous zinc-ion symmetric cell, an aqueous zinc-ion half-cell, and an aqueous zinc-ion full cell were assembled according to the steps of Example 1.
[0146] Performance tests were conducted, and the results are shown in Table 1.
[0147] Comparative Example 5
[0148] Using the aqueous zinc-ion electrolyte containing functional additives from Comparative Example 1, an aqueous zinc-ion full cell was assembled according to the steps of Example 8.
[0149] Performance tests were conducted, and the results are shown in Table 1.
[0150] Comparative Example 6
[0151] Using the aqueous zinc-ion electrolyte containing functional additives from Comparative Example 2, an aqueous zinc-ion full cell was assembled according to the steps of Example 8.
[0152] Performance tests were conducted, and the results are shown in Table 1.
[0153] Comparative Example 7
[0154] Using the aqueous zinc-ion electrolyte containing functional additives from Comparative Example 3, an aqueous zinc-ion full cell was assembled according to the steps of Example 8.
[0155] Performance tests were conducted, and the results are shown in Table 1.
[0156] Comparative Example 8
[0157] Using the aqueous zinc-ion electrolyte containing functional additives from Comparative Example 4, an aqueous zinc-ion full cell was assembled according to the steps of Example 8.
[0158] Performance tests were conducted, and the results are shown in Table 1.
[0159] Table 1. Performance of Aqueous Zinc-Ion Batteries
[0160]
[0161] from Figure 1 It can be seen that the zinc symmetric battery using an electrolyte containing 0.1 mol / L Al(OTf)3 additive can maintain a polarization voltage below 50 mV during more than 2000 hours of cycling, while the zinc symmetric battery using a blank electrolyte loses control of its polarization voltage after 50 hours, indicating that it may have broken down due to excessive dendrite growth. This proves that the 0.1 mol / L Al(OTf)3 additive can significantly inhibit dendrite reactions during zinc-ion battery cycling and improve cycle reversibility.
[0162] from Figure 2 It can be seen that the cycle life and coulombic efficiency of Zn-Cu half-cells differ after adding different concentrations of Al(OTf)3 additive. Among them, the half-cell with 0.1 mol / L Al(OTf)3 added showed the longest cycle life and the highest average coulombic efficiency, indicating that 0.1 mol / L is the ideal concentration of Al(OTf)3 additive.
[0163] from Figure 3 , Figure 4 As can be seen from Table 1, adding 0.1 mol / L of M(OTf) n The aqueous zinc-ion batteries with the additives exhibited significantly improved specific capacity when using both CNT-MnO2 and I2-PAC cathodes. This is attributed to M... n+ The intercalation stabilizing effect of CNT-MnO2 and [OTf] - The oxidation and fixation of polyiodide ions at the I2-PAC cathode is significant. Full cells using 0.1 mol / L Al(OTf)3 as an additive exhibit particularly high specific capacity and retention. This may be due to the role of Al... 3+This is due to the combination of the highest fit to the MnO2 structure and the highest [OTf]- concentration of Al(OTf)3 under the condition of equal oxygen ion concentration;
[0164] from Figure 5 It can be seen that after 50 cycles of constant current charge and discharge, the zinc foil surface of the symmetric battery using 0.1 mol / L Al(OTf)3 as an electrolyte additive showed XPS characteristic peaks of AlF3 (F 1s 687.2 eV, Al 2s 121.6 eV, Al 2p 76.7 eV), indicating that an AlF3 interface layer was generated in situ on the negative electrode surface after cycling. This layer helps to further suppress the corrosion and hydrogen evolution of the zinc negative electrode during cycling. At the same time, the low nucleation energy barrier between AlF3 and the zinc (002) crystal plane can induce uniform and fine-grained zinc deposition, thereby further extending the reversibility and stability of the battery cycle.
[0165] from Figure 6 It can be seen that after placing commercial zinc foil in 2 mol / L ZnSO4 and 2 mol / L ZnSO4 + 0.1 mol / L Al(OTf)3 for 24 h, the grain size formed on the surface of the zinc foil placed in the electrolyte containing 0.1 mol / L Al(OTf)3 was significantly smaller than that of the control group, and the distribution was also more uniform and dense. This may be due to the Al 3+ The addition of [a substance] alters the solvation structure of the electrolyte, thereby slowing down the rate of surface byproduct formation and inhibiting the corrosion process of the zinc anode.
[0166] As can be seen from Comparative Examples 2 and 6 in Table 1, using the full [OTf]... - In environmental conditions, due to its relatively simple mechanism of action, and [OTf] - Its transport properties in aqueous solution are inferior to those of SO4. 2- While flexible, its improvement on battery performance is very limited. Furthermore, since zinc trifluoromethanesulfonate is generally much more expensive than zinc sulfate heptahydrate, using full [OTf] is not recommended. - The cost-effectiveness of environmental improvements for performance enhancement is clearly poor. Furthermore, as can be seen from Comparative Examples 3-4 and 7-8 in Table 1, using [OTf] alone... - Or Al 3+ When used as an additive, its mechanism for improving battery performance remains relatively simple, and its performance enhancement is also limited. This explains why using a large amount of conventional zinc source + a small amount of [OTf]... - Anionic / heterovalent cationic composite additives are a reasonable modification approach.
[0167] In summary, this invention involves adding a trifluoromethanesulfonic acid metal salt M(OTf) to an aqueous zinc ion electrolyte. n Its non-zinc metal cation M n+ Adjustable Zn2+ The solvated structure reduces bound water to suppress hydrogen evolution at the zinc anode, reduces byproducts, and improves cycle reversibility. The anions and cations can also form a fluoride (MF) protective layer on the zinc anode, preventing corrosion and inducing uniform zinc deposition, thus extending lifespan. For vanadium / manganese / nickel / cobalt-based cathodes, M... n+ It can be embedded in a stable crystal structure to slow down dissolution and collapse, thereby reducing capacity decay; for iodine-containing cathode materials, trifluoromethanesulfonate can fix polyiodides, suppress shuttle effect, reduce loss of active material, zinc corrosion and self-discharge, thereby improving the performance of aqueous zinc-ion batteries.
[0168] All aspects, embodiments, and features of this invention should be considered illustrative in all respects and not limiting of the invention; the scope of the invention is defined only by the claims. Other embodiments, modifications, and uses will become apparent to those skilled in the art without departing from the spirit and scope of the invention as claimed.
[0169] In the preparation method of this invention, the order of the steps is not limited to the listed order. For those skilled in the art, variations in the order of the steps without creative effort are also within the scope of protection of this invention. Furthermore, two or more steps or actions can be performed simultaneously.
[0170] Finally, it should be noted that the specific embodiments described herein are merely illustrative examples of the invention and are not intended to limit the implementation of the invention. Those skilled in the art can make various modifications or additions to the described specific embodiments or use similar methods to replace them; it is neither necessary nor possible to exemplify all embodiments here. However, these obvious variations or modifications derived from the essential spirit of the invention still fall within the scope of protection of the invention, and interpreting them as any additional limitation would contradict the spirit of the invention.
Claims
1. An aqueous zinc ion electrolyte containing functional additives, characterized in that, Includes zinc salts, functional additives, and solvents; The functional additive is a trifluoromethanesulfonic acid metal salt, wherein the metal element is selected from at least one of aluminum, magnesium, manganese, tin, and indium; The concentration of the functional additive in the aqueous zinc ion electrolyte containing the functional additive is 0.01-1 mol / L.
2. The aqueous zinc ion electrolyte containing functional additives according to claim 1, characterized in that, The concentration of functional additives in the aqueous zinc ion electrolyte is 0.05-0.3 mol / L.
3. The aqueous zinc ion electrolyte containing functional additives according to claim 1, characterized in that, The concentration of zinc salt in the aqueous zinc ion electrolyte is 0.1-5 mol / L.
4. The aqueous zinc ion electrolyte containing functional additives according to claim 1, characterized in that, The zinc salt is selected from at least one of zinc sulfate, zinc nitrate, zinc trifluoromethanesulfonate, zinc bis(trifluoromethanesulfonyl)imide, zinc chloride, zinc acetate, and zinc perchlorate.
5. The aqueous zinc ion electrolyte containing functional additives according to claim 1, characterized in that, In the aqueous zinc ion electrolyte, the concentration of the zinc salt is greater than the concentration of the functional additive.
6. A method for preparing an aqueous zinc ion electrolyte containing functional additives as described in claim 1, characterized in that, The preparation method includes: dissolving functional additives in water in an inert gas environment, then adding zinc salts to obtain an aqueous zinc ion electrolyte containing functional additives.
7. An aqueous zinc-ion battery, characterized in that, It includes the aqueous zinc ion electrolyte containing functional additives as described in any one of claims 1-5, or the aqueous zinc ion electrolyte containing functional additives prepared by the preparation method of the aqueous zinc ion electrolyte containing functional additives as described in claim 6.
8. The aqueous zinc-ion battery according to claim 7, characterized in that, The aqueous zinc-ion battery includes an aqueous zinc-ion symmetric battery, an aqueous zinc-ion half-cell, and an aqueous zinc-ion full-cell.
9. The aqueous zinc-ion battery according to claim 7, characterized in that, The aqueous zinc-ion symmetric battery includes an aqueous zinc-ion electrolyte containing functional additives, a diaphragm, and a zinc negative electrode. The aqueous zinc-ion half-cell includes a current collector, an aqueous zinc-ion electrolyte containing functional additives, a diaphragm, and a zinc negative electrode. The aqueous zinc-ion full battery includes a positive electrode, an aqueous zinc-ion electrolyte containing functional additives, a separator, and a zinc negative electrode.
10. The aqueous zinc-ion battery according to claim 9, characterized in that, The positive electrode material in the positive electrode sheet is selected from at least one of manganese-based compounds, vanadium-based compounds, nickel / cobalt-based compounds, elemental iodine, and composite materials.
